2014
DOI: 10.3892/ijo.2014.2596
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-449 suppresses proliferation of hepatoma cell lines through blockade lipid metabolic pathway related to SIRT1

Abstract: MicroRNA (miRNA or miR) inhibition of oncogenic related pathways has been shown to be a promising therapeutic approach for cancer. SIRT1 might be a promoter factor on tumorigenesis of hepatocellular carcinoma (HCC). However, the mechanism is unknown. We investigated whether miRNAs regulate the SIRT1 and its downstream SREBP-lipogenesis-cholesterogenesis metabolic pathway in hepatoma cells. Human hepatoma cells were transfected with miR-449 mimics and inhibitors, and the effects of miR-449 on cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 73 publications
3
36
0
Order By: Relevance
“…SIRT1 could affect growth arrest, cell death, DNA damage repair, and metabolism and is associated with life span and cancer risk . SIRT1 may play as an oncogene or a suppressor in tumor based on the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 could affect growth arrest, cell death, DNA damage repair, and metabolism and is associated with life span and cancer risk . SIRT1 may play as an oncogene or a suppressor in tumor based on the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…miR-34 was confirmed to be a tumor suppressor, and its level was relatively low in the cardiovascular system. Similarly, previous studies also suggested that miR-449a was a tumor suppressor in numerous cancer types by targeting different target genes [8, 26, 27]. Moreover, a number of studies recently indicated the downregulation of the expression of miR-449 in various human malignancies, including lung cancer, prostate cancer, and adrenal hyperplasia [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that specifically bind to target mRNAs and thus downregulate gene expression by degradation or translational repression [8, 9]. Recently, these molecules have been implicated in several processes of direct relevance to the heart, including cardiac development, cardiac hypertrophy, heart failure, and angiogenesis [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 increases the level of LXR [38] and decreases SREBP [40]; remarkably, SIRT1 itself is targeted by miR-34a [41, 42], miR-132 [43], miR-204-5p [44], miR-499 [45], and many others.…”
Section: Micrornas Involvement In Lipid Metabolismmentioning
confidence: 99%